Cost Management by Applying Resource Consumption Accounting Technique to Enhance Corporate Governance (Zien Journal of Social Sciences and Humanities, 2023)
The research aims to shed light on the cognitive aspect of some contemporary techniques in cost management represented by the technique of accounting for resource consumption and its role in strengthening corporate governance and explaining the role played by corporate governance with its various procedures in managing the cost of the product by reducing it and maintaining its quality. On the systematic nature on which the resource consumption accounting technique is applied and the impact of this technique on achieving success in terms of applying corporate governance procedures. The most important findings of the research were that the methodology of working with the resource consumption accounting technique in light of the competitive business environment provides detailed information about the causes of cost at the level of resource pools as well as at the level of activities, and this supports the short-term differential decision-making process, moreover, resource consumption accounting is classified Costs are proportional and fixed according to the principle of causation, which provides the possibility of isolating idle/excess energy costs, and this supports long-term decisions related to the allocation of resources and energy. These technologies, which focus on the efficient utilization of available resources and maximizing the value of the company, and this supports corporate governance in reducing waste and preserving the company's resources.